A Case Study of Indonesian Journalists’ Participation in a Cochran Fellowship Program focused on Biotechnology and Journalism - Holli R. Leggette; Samuel Thomas Hall; Theresa Pesl Murphrey (Journal of International Agricultural and Extension Education, 2017)
This case study describes the participation of Indonesian journalists in a two-week Cochran Fellowship Program designed to teach about biotechnology and the process of disseminatings cientific information. The purpose of this case study was to examine the experience of Indonesian journalists who participated in science communication training in an effort to document practices that improve journalistic writing skills and encourage positive perceptions of biotechnology. Therefore, we collected pre- and post-training reflections, photo reflections, and project debriefing session reflections from six Indonesian journalists who specialized in various types of journalism and worked for private or government-owned news organizations. The reflections revealed changes in comfort level with journalistic writing, thoughts and behaviors, and understanding of the biotechnology process. The journalists showed the most change in comfort level for explaining communication tools; using, evaluating, and choosing communication mediums; and translating science related to biotechnology. They described biotechnology as a highly debated, multi-step process affecting food security and noted that they gained valuable information about science journalism and biotechnology. Training journalists and understanding their voices could enable agriculturalists to more effectively communicate about scientific issues and develop impactful capacity-building activities. Because journalists have the power to inform and influence, programs, like this one, can have far-reaching, beneficial impacts on the adoption of biotechnology. However, researchers should investigate future programs using a longitudinal study to determine if programs influence the stories published in the years following the training.
Keywords: biotechnology; science journalism; United States agriculture; photovoice